2008
DOI: 10.1093/brain/awn099
|View full text |Cite
|
Sign up to set email alerts
|

Response monitoring, repetitive behaviour and anterior cingulate abnormalities in autism spectrum disorders (ASD)

Abstract: Autism spectrum disorders (ASD) are characterized by inflexible and repetitive behaviour. Response monitoring involves evaluating the consequences of behaviour and making adjustments to optimize outcomes. Deficiencies in this function, and abnormalities in the anterior cingulate cortex (ACC) on which it relies, have been reported as contributing factors to autistic disorders. We investigated whether ACC structure and function during response monitoring were associated with repetitive behaviour in ASD. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
276
3
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(327 citation statements)
references
References 116 publications
31
276
3
5
Order By: Relevance
“…These deficits can also be linked with performance monitoring difficulties. Performance monitoring (also referred to as response monitoring) involves the process of evaluating the consequences of behavior and making adjustments to optimize outcomes (Thakkar et al, 2008). This appears to be problematic for individuals with ASD Thakkar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These deficits can also be linked with performance monitoring difficulties. Performance monitoring (also referred to as response monitoring) involves the process of evaluating the consequences of behavior and making adjustments to optimize outcomes (Thakkar et al, 2008). This appears to be problematic for individuals with ASD Thakkar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Performance monitoring (also referred to as response monitoring) involves the process of evaluating the consequences of behavior and making adjustments to optimize outcomes (Thakkar et al, 2008). This appears to be problematic for individuals with ASD Thakkar et al, 2008). Difficulties with performance monitoring in ASD have been proposed to result from structural and functional abnormalities in the anterior cingulate cortex (ACC), which were also related to higher ratings of repetitive behavior (Thakkar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a very heterogeneous group. Consistent findings in these studies were reduced FA in the CC Lee et al, 2009;Shukla et al, 2010Shukla et al, , 2011b in the superior temporal gyrus (Cheung et al, 2009;Lee et al, 2007Lee et al, , 2009Shukla et al, 2011a); the anterior cingulate cortex (Cheng et al, 2010;Thakkar et al, 2008); the frontal lobe (Cheng et al, 2010;Shukla etl al., 2011a;Sundaram et al, 2008); the thalamus (Lee et al, 2009) and the interior and posterior limbs of the internal capsule (Cheng et al, 2010;Shukla et al, 2010). (Catani et al, 2008).…”
Section: Dti Findings In Autism: Review Of Published Articlessupporting
confidence: 60%
“…[8][9][10][11] Finally, there are now many DTI studies that have consistently demonstrated abnormalities in FA in the brains of ASD participants. [12][13][14][15][16][17] Because FA is a widely accepted measure of the structural integrity of white matter, 18 these studies have collectively demonstrated a pattern of findings consistent with neural disconnectivity in ASD. However, given the significant heterogeneity in methodologies and participants in these studies, it is difficult to identify a common underlying pattern of neuropathology across all studies.…”
mentioning
confidence: 97%